2008
DOI: 10.1111/j.1365-3059.2008.01833.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidases in the early responses of different potato cultivars to infection by Potato virus YNTN

Abstract: Peroxidases (POXs) were investigated in three cultivars of potato ( Solanum tuberosum ) with different susceptibilities to infection by Potato virus Y NTN ( PVY NTN ). Soluble, ionically-bound and covalently-bound POXs were analysed over 24 h post inoculation (hpi) in bottom inoculated leaves, upper intact leaves, and in roots. The first changes were observed at 3 hpi when the activity of ionically-bound POXs increased significantly in the inoculated leaves of tolerant cv. Pentland Squire and of resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…After 4 weeks growth in soil, the potato plants of each cultivar were divided into two groups of 15–18 plants each: virus‐inoculated and mock‐inoculated groups. The PVY NTN (isolate NIB‐NTN, G en B ank accession number AJ585342) inoculation procedure was carried out according to Milavec et al. (2008).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…After 4 weeks growth in soil, the potato plants of each cultivar were divided into two groups of 15–18 plants each: virus‐inoculated and mock‐inoculated groups. The PVY NTN (isolate NIB‐NTN, G en B ank accession number AJ585342) inoculation procedure was carried out according to Milavec et al. (2008).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the study by Whitham et al (2003) showed that the major differences in gene expression in Arabidopsis thaliana occurred 3-5 days rather than 1 or 2 days following inoculation with five different viruses. However, our experiment was based on previous studies, in which potato plants responded to PVY NTN at the biochemical level as early as 3 hpi (Milavec et al, 2008).…”
Section: Transcriptome Response In the Early Reaction To Virus Inoculmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of reports have indicated an increase in POX activity during or after PVY attack in both compatible and incompatible interactions (Nie 2006; Doubnerova et al. 2007; Milavec et al. 2008).…”
Section: Discussionmentioning
confidence: 99%